Comparison in formation, optical properties and applicability of DC magnetron and RF sputtered aluminum oxide films. (June 2016) - Serényi, M.; Lohner, T.; Sáfrán, G.; Szívós, J.
Abstract: Amorphous aluminum oxide (a-Al2 O3, alumina) can be widely used for ceramic coatings, gate oxide for microelectronics and waveguiding component of integrated optical elements. Moreover, it is a candidate for masks and molds for the preparation of new generation nanoscale devices. Among different technological procedures, cathode sputtering is one of the most effective techniques to deposit amorphous materials which could not be vitrified by an ordinary melting method. Here, the structural and optical properties of Direct Current (DC) magnetron and Radio Frequency (RF) sputtered alumina layers have been revealed regarding to the preparation method. It is shown that the optical absorption and the refractive index of the RF sputtered alumina enable the films to be used as high quality waveguiding material. The oxygen incorporation from the plasma with higher oxygen content results in a bandgap shift to the lower values. Contrarily, reactive DC magnetron sputtering process led to only partly oxidized film growth exhibiting higher absorption. Highlights: Wafer of ceramic served as target for the RF sputtering process of alumina layer. The amorphous layers practically have no absorption in the range of 350–600 nm. The role of the excess oxygen for the optical absorption of the RF sputtered amorphous alumina.